Climate projections over the Antarctic Peninsula region to the end of the 21st century. Part 1: cold temperature indices - A. Chyhareva; S. Krakovska; D. Pishniak (Ukrainian Antarctic Journal, 2019)
Objective. This paper deals with an estimation of the climate change at the Antarctic Peninsula region. During last decades, the most significant warming is observed in Polar regions, particularly in the Antarctic Peninsula region, where the Ukrainian Antarctic Akademik Vernadsky station is located. Therefore, the providing of the complex estimation of climate change trend is an important task for the region. These changes are taking place nowadays and will happen in the future. So, the main objective of the study is to estimate changes of climate characteristics in the Antarctic Peninsula region in the 21st century, based on calculation of the relevant climate indices. The projections of the temperature and precipitation characteristics in the Antarctic Peninsula region and Akademik Vernadsky station area for RCP4.5 and RCP8.5 scenarios are the objects of the research. Methods of the research are numerical simulation and statistical analysis of the regional climate model data for the Antarctic Peninsula region from the International Project Polar-CORDEX. Spatial distribution of this data is 0.44° and three periods are under consideration: historical climatic period (1986—2005) and two future periods 2041—2060 and 2081—2100. The R-code language and the modified computing code developed by Climate4R Hub project in Jupiter Notebook environment were used for climate data analysis in this research. Six parameters were chosen to estimate climate change in the Antarctic Peninsula region: number of frost days with minimal air temperature (Т) less 0 °C, number of ice days with maximal Т less 0 °C, annual total precipitation, mean precipitation rate, maximum yearly duration of periods without precipitation, maximum yearly duration of periods with precipitation more than 1 mm per day. Results as an analysis of the cold temperature indices are presented in the Part I of the paper, while an analysis of the wet/dry indices will be presented in the Part II of the paper. Conclusions. Over the Antarctic Peninsula region, both scenarios project an average decrease in the cold season period. This process will be more pronounced for the RCP 8.5 scenario, when even to the middle of the century the period with negative temperatures is rapidly decreasing over the Larsen Ice Sheet area, which may cause its total or partial collapse. Over Akademik Vernadsky station area, the climate indices changes will almost triple as high as the averaged values over the Antarctic Peninsula for the two scenarios, indicating a greater vulnerability to the climate change in the area.